Step-NC code generator for drilling operation using GEN-M - Zamri Tan, Nurul Zakiah (2012)
STEP-NC used to transfer machining data between STEP-NC compliant Computer Aided Design (CAD), Computer Aided Manufacturing (CAM) and Computer Numerical Controller (CNC). It has gain worldwide consent when International Standard of Organization (ISO) has established a new data model for ISO 14649. By implementing STEP-NC, profitable and intelligent manufacturing are very convincing. It overcomes G & M code weakness which has thousand lines of codes but none of them define the machining process. In order to create a complete chain of STEP-NC system to be a new way of producing product in manufacturing environment, a new CNC machine and CAM software that compliant to STEP-NC has to be developed. This research is a software development that name as GEN-M using Visual Basic.Net 2010. The success of GEN-M development contributed a new application to serve new manufacturing environment in generating STEP-NC code for machining. Although there are many researches produces new application software, GEN-M can be a variety of CAM software that compliant to STEP-NC. More over GEN-M have few attractive functions such as redirecting users to a website for seeking about STEP-NC information; email the generated STEP-NC program to other parties and more. GEN-M is successfully developed where the verification process which is the generated code by GEN-M is compared to ISO 14649 Part 11 gave less number of different with reasonable cause and more similarities for related entities. Therefore the software is capable to generate code for drilling referring to selected case study from Annex F (Example 1) in ISO 14649 Part 11. This research can be a stepping stone to the next level of research.